Antropologia perante as cotas raciais (2000-2010): raça e projeto de nação - Ventura, Millena Juliette Teles Moraes (2025)
This thesis investigates how the implementation of racial quotas in higher education was addressed in Brazilian anthropological production between 2000 and 2010. The central objective is to understand how the debate on affirmative action impacted the discipline, generating conceptual disputes over race, nation-building, and the role of anthropology in the formulation of public policies. Specifically, the study examines how racial quotas became an anthropological public issue, identifying key theoretical divergences among researchers, analyzing the mobilization of concepts such as justice and affirmative action, and investigating the tensions arising from the different academic and institutional positions of scholars. To conduct the research, both qualitative and quantitative approaches were employed, including an analysis of articles published in academic journals, a mapping of the academic trajectories of scholars involved in the debate, and their participation in public arenas, such as manifestos in favor of or against racial quotas. The longitudinal analysis made it possible to observe how anthropological production was affected by the controversy at different moments, while the study of intellectual networks highlighted the centrality of certain universities in the debate. The findings indicate that anthropology not only reflected the political and social disputes surrounding racial quotas but also underwent internal transformations, reassessing its categorizations and theoretical articulations.